2015
DOI: 10.1016/j.visres.2015.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical properties of photoreceptors in Corixa punctata facilitate diurnal life-style

Abstract: Measurement of evolutionary adaptations of a visual system to its visual and operational ecology requires comparison of visual function in different species with similar morphologies and visual ecologies, occupying the same habitats but displaying differences in visually-guided behavior. The goal here was to document the biophysical properties of photoreceptors in the lesser water boatman Corixa punctata, which shares many features with the previously studied aquatic predator water boatman backswimmer Notonect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 21 publications
3
32
0
Order By: Relevance
“…However, when only the first 10 repeats were used, the average IR max was 33±12 bits s −1 , indicating a drastic decrease in information capacity for prolonged responses in moderately bright light (however, the residual noise level is 1.73 times higher when 10 repetitions are used for signal estimation instead of 30). Similar to several other species Frolov and Weckström, 2014;Frolov, 2015;Immonen et al, 2014a), a positive correlation was found between photoreceptor capacitance, a proxy for cell size, and maximal information rate.…”
Section: Elementary Responses To Lightsupporting
confidence: 81%
See 3 more Smart Citations
“…However, when only the first 10 repeats were used, the average IR max was 33±12 bits s −1 , indicating a drastic decrease in information capacity for prolonged responses in moderately bright light (however, the residual noise level is 1.73 times higher when 10 repetitions are used for signal estimation instead of 30). Similar to several other species Frolov and Weckström, 2014;Frolov, 2015;Immonen et al, 2014a), a positive correlation was found between photoreceptor capacitance, a proxy for cell size, and maximal information rate.…”
Section: Elementary Responses To Lightsupporting
confidence: 81%
“…To evaluate photoreceptor performance, two contrast-modulated light stimuli, a naturalistic and Gaussian white-noise, were used as described previously (Frolov, 2015). The white-noise stimulus was made of 30 repetitions of a 2 s Gaussian randomly modulated sequence preceded by an adapting 1 s steady light to accommodate the initial depolarizing transient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Part of the data presented in this study were obtained from previously published work on C. morosus , C. punctata (Frolov 2015), D. melanogaster (Krause et al 2008), G. lacustris , G. bimaculatus , N. glauca (Immonen et al 2014a), and P. americana (Immonen et al 2014b). Additional experiments were performed on P. xuthus, generously provided by Prof. Kentaro Arikawa (Sokendai, Hayama, Japan), G. integer, generously provided by Petri Niemelä (Munich, Germany), C. vicina, P. schultei, and G. portentosa, purchased from Blades Biological (Edenbridge, UK), and A. mellifera, E. lapponicus, and M. roeselii, which were caught locally in Oulu (Finland).…”
Section: Electrophysiologymentioning
confidence: 99%